Assessing Influencer Engagement Methods for Calculating Fees Based on Customer Reengagement - Ananda, Zulkifli (Journal of Social Commerce, 2023)
In this study, different influencer engagement approaches are compared on how well they predict purchaser reengagement and a formula for pricing influencers is described based on these methods. Through the content material evaluation of tailor-made content material, put up frequency, interactive campaigns, and influencer statements, the study found personalisation as the maximum powerful approach with interactions followed by campaigns, frequency of posts, and influencer testaments displaying minimal impact. The highest engagement degrees were identified to originate from the extra ordinary influencer classifications while niche differences in the levels of engagement were also evident and indeed compared were made particularly in the context of style. To some extent, this adds to the knowledge is lacking on how engagement initiatives influence reengagement and how to calculate rate. The outcomes present invaluable steerage for these looking for to enhance influencer advertising and marketing strategies and for many who must make records-based resolution.